Engineering Aerosol‐Resilient EV‐Liposome Hybrid Vesicles for Inhalable Nintedanib Delivery in Pulmonary Fibrosis - Xin Yan; Qi Zhang; Jing Xu; Hengkai Qi; Jing Bian; Honglian Zhao; Aiping Zang; Lingmin Zhang; Xueli Huang; Xi Kang; Jun Zhu; Dandan Xiao; et al. (Advanced Healthcare Materials, 2026)
ABSTRACT Extracellular vesicles (EVs) are promising biomimetic nanocarriers for pulmonary delivery, but their inhalation translation is limited by membrane fragility under aerosol‐induced shear and air‐liquid interfacial stress. Here, we developed an EV‐liposome hybrid vesicle formulation (NIN@SV) for inhalable delivery of nintedanib and identified a composition‐dependent balance between EV‐derived biological functionality and aerosol robustness. An optimized EV protein:NIN@LP lipid mass ratio of 3:7 enhanced mucus penetration and cellular association while minimizing post‐nebulization size drift and preserving aerodynamic performance. Density‐gradient fractionation and physical‐mixture controls supported the formation of a hybrid vesicle‐enriched population rather than simple coexistence of unfused EVs and liposomes. In parallel, FRET‐assisted membrane‐proximity analysis, calibrated using disruption controls, indicated improved resistance of NIN@SV to aerosol‐induced membrane perturbation. Functionally, NIN@SV enhanced formulation‐associated cellular association, prolonged pulmonary retention, and attenuated bleomycin‐induced pulmonary fibrosis under the tested nominal inhaled dosing regimen. Mechanistically, NIN@SV suppressed fibroblast activation and attenuated pro‐fibrotic macrophage‐associated features. Together, these findings support an aerosol‐resilient EV‐liposome membrane‐engineering strategy and provide a practical design rationale for inhalable hybrid vesicles in pulmonary drug delivery.